External Economic Factors Of Development Of The Industrial Structure Of The Economy Of The Pacific Russia - A.V., MOSHKOV (The journal of contemporary issues in business and government, 2021)
The socio-economic development of Pacific Russia is traditionally associated with the active involvement of its natural resource and production potential in the integration processes of the Asia-Pacific region of the world. An important factor that stimulates the foreign economic activity of production is also the favorable economic and geographical position of the region. The aim of the work is to study the influence of foreign economic factors on the formation of the sectoral structure of the subjects of the Far Eastern Federal District (FEFD). Currently, the positive effect of foreign economic activity in the regions is limited to the "backward" structure of the economy of most subjects of the Far Eastern Federal District (a high share of extractive industries, poor development of manufacturing and services), which has developed due to the uneven distribution of demographic, production and infrastructure potentials. To assess the uneven development of subjects, it is proposed to use the methods of sectoral analysis of the economy, as well as the method of zoning the territory of the Far Eastern Federal District by the specifics of economic activity, incl. commodity structure of exports and imports. Thus, on the territory of Pacific Russia, there are two zones of economic development - 1) "northern" and 2) "southern", differing in the combination of factors and living conditions of the population, the sectoral structure of the economy and foreign economic activity. The subjects of the "southern" zone are distinguished by a higher level of demographic, production and infrastructural potential, as well as a relatively high share of processing and service activities in the sectoral structure of the economy. At the same time, a common feature of all regions of Pacific Russia is noted - the predominance in the commodity structure of exports of products with low added value (raw materials and materials), and in the structure of imports - products of manufacturing industries (machinery and equipment).